Feeding Behavior Associated With Gastric Cancer - Kiyana Kasiri; Farkhondeh Amin-Shokravi; Hossein Shahnazi (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: Preparing educational programs related to prevention of prevalent diseases like cancer is considered a health necessity. The aim of this paper was to study the impact of feeding behavior associated with gastric cancer in women working in Isfahan in 2013. Methods: In this semi-experimental interventional study, 72 female workers were classified into two case and control groups, each 36 workers. Inclusion criteria of the study were: Iranian nationality, female workers, married, educated, having at least 20 years, and residents of Isfahan. Data was gathered using a questionnaire (=0.810). Based on the results of pre-test, the nutrition educational package was designed to suit the training needs. The experimental group received the educational intervention (six45-minutes sessions in six weeks).Then immediately and three months after educational intervention both groups were asked to complete the questionnaire again. Data was analyzed using independent T test with alpha level of 0.05. The study was approved by the Tarbiat Modress University's Medical Ethics Committee. Results: The mean age of cases was 33.12 and control group 33.22, significant difference (p<0.001) in case and control groups in mean awareness (89.72 vs. 36.85), attitude (69.50 vs. 34.98) and practice (75.63 vs. 40.22) after the intervention. Conclusion: The effectiveness of nutrition educational package showed a developed accretion of knowledge, attitude and practice of employed women in feeding behavior associated with gastric cancer. Paper Type: Research Article.